PERBEDAAN PENGGUNAAN INTENSITAS CAHAYA LAMPU TERHADAP HASIL TANGKAPAN BAGAN APUNG DI PERAIRAN SELAT ROSENBERG KABUPATEN MALUKU TENGGARA KEPULAUAN KEI - Julianus, Notanubun; Patty, Wilhelmina (JURNAL PERIKANAN DAN KELAUTAN TROPIS, 2010)
One of potential fishing grounds for small pelagic fish in Southeast Mallucas Regency is Rosenberg Strait waters. In this region, a study on the effect of different light intensities of floating lift net on fish catches was carried out. The analyses were done on light distribution of 4 light intensities different: Petromaks Lamp and Underwater Lamps of each 18 watt, 36 watt and 54 watt. This study showed that catches of floating lift net using different light intensities were statistically significantly different. The use of 36 watt and 54 watt underwater lamp yielded the same amount of catches but higher than that of 18 watt-underwater lamp and petromaks, both in number and species. Catches consisted of 17 species, 16 fishs and 1 mollusca. Number of species and size also varied with light intensity used. There were 13 fishs species dominated by Stolephorus indicus as much as 46.9 kg or 22% for petromaks catches, 14 fishs species dominated by Rastrelliger kanagurata as much as 64 kg (31%) for 18 watt underwater lamp, 17 fishs species dominated by Rastrelliger kanagurata as much as 76 kg (28%) for 36 watt underwater lamp, and 15 fishs species dominated by Stolephorus devisi as much as 54.8 kg (22%) for 54 watt underwater lamp, respectively. Based on the results, it is recommended that the use of light intensity in fishing operations of floating lift net should be 36 watt and 54 watt underwater lamps, due to high catches, both in number and species. Beside that, since light fishing has also caught illegal fish size, number of this fishing gear type should be controlled.